INFECTIOUS STUNTING SYNDROME IN CHICKENS - A. Abdul-Aziz, Tahseen (The Iraqi Journal of Veterinary Medicine, 1987)
An infectious syndrome of broiler chickens characterized by. stunted growth, poor feathering, leg weakness, poor feed conversion, and loss of pigmentation of the skin. The syndrome was initially reported in Netherland (Kouwenhoven et al., 197848), and have since been described in England (Bracewell and Wyeth, 1981), U.S.A. (page et al., 1982), Australia (pass et al.,1982) and Canada (Riddell and Derow, 1982). The various names of the syndrome reflects the variety of clinical signs and gross lesions .observed, and although reported conditions share many clinical signs and pathological changes, it is not certain that all reports describe the same disease entity.